Dual Mode of the Saponin Aescin in Plant Protection: Antifungal Agent and Plant Defense Elicitor - Trdá, Lucie; Janda, Martin; Macková, Denisa; Pospíchalová, Romana; Dobrev, Petre I.; Burketová, Lenka; Matušinsky, Pavel (Frontiers in Plant Science, 2019)
Being natural plant antimicrobials, saponins have potential for use as biopesticides. Nevertheless, their activity in plant–pathogen interaction is poorly understood. We performed a comparative study of saponins' antifungal activities on important crop pathogens based on their effective dose (EC50) values. Among those saponins tested, aescin showed itself to be the strongest antifungal agent. The antifungal effect of aescin could be reversed by ergosterol, thus suggesting that aescin interferes with fungal sterols. We tested the effect of aescin on plant–pathogen interaction in two different pathosystems: Brassica napus versus (fungus) Leptosphaeria maculans and Arabidopsis thaliana versus (bacterium) Pseudomonas syringae pv tomato DC3000 (Pst DC3000). We analyzed resistance assays, defense gene transcription, phytohormonal production, and reactive oxygen species production. Aescin activated B. napus defense through induction of the salicylic acid pathway and oxidative burst. This defense response led finally to highly efficient plant protection against L. maculans that was comparable to the effect of fungicides. Aescin also inhibited colonization of A. thaliana by Pst DC3000, the effect being based on active elicitation of salicylic acid (SA)-dependent immune mechanisms and without any direct antibacterial effect detected. Therefore, this study brings the first report on the ability of saponins to trigger plant immune responses. Taken together, aescin in addition to its antifungal properties activates plant immunity in two different plant species and provides SA-dependent resistance against both fungal and bacterial pathogens.